Data Efficient Paradigms for Personalized Assessment of Black-Box Taskable AI Systems - Verma, Pulkit (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
The vast diversity of internal designs of taskable black-box AI systems and their nuanced zones of safe functionality make it difficult for a layperson to use them without unintended side effects. My dissertation focuses on developing paradigms that enable a user to assess and understand the limits of an AI system’s safe operability. We develop a personalized AI assessment module that lets an AI system execute instruction sequences in simulators and answer queries about these executions. Our results show that such a primitive query-response interface is sufficient to efficiently derive a user-interpretable model of a system’s capabilities.